Business economics and managerial decision making - Jones, T. T. (J. Wiley, 2004)
Written primarily for students taking℗¡courses in managerial economics℗¡in Britain and Europe, ℗¡The Business Economics and Managerial Decision Making analyses the growth and development of privately owned firms and also the decisions made by firms operating in both private and public sector enterprises. Coverage is clear and concise, and avoids specialist techniques such as linear programming, which in a European context tend to belong in courses dealing with operations research. The book also avoids straying into areas of industrial economics, instead retaining a sharp focus on relevant issues.- Resumé vydavatel